Pendidikan Anak Usia Dini Serta Implementasinya dalam Pendidikan Formal dan Informal - Junanah Junanah (EL-TARBAWI, 2011)
Every child is born holy in nature. Therefore, whether he/ she is bad or good in the future is on parents’ hand. Early childhood is a critical phase in human development throughout life span. How parents treat and develop their children will determine how they will be in their adulthood. If parents use effective and good ways in maturing and nurturing their children, they will grow well. Yet, in contrary, if parents do not do so or fail in nurturing their children, they will grow immature. In this issue, early childhood education takes an important role in children development. This paper will discuss early childhood education and how to apply it in a formal (i.e. playgroups), as well as in an informal (i.e. home parenting) education. Several theories and practices are presented in this current paper. In sum, this article found that formal early childhood education cannot stand alone without significant support from the informal one. Both formal and informal early childhood education should run together in a mutual practices and frameworks.